Troubles in paradise - Hilderbrand, Elin (New York : Little, Brown and Company, 2020)
Irene Steele has just settled in at the villa on St. John with her sons after her husband$1 (Bs death. But through a visit from the FBI, Irene once again learns just how little she knew about the man she loved. As a storm gathers strength in the Atlantic, surprises are in store for the Steeles: at last all will be revealed about the secrets and lies that brought Irene and her sons to St. John -- and the truth that transformed them all. s
Series numeration from author's website.
A novel.
Keywords: Widows -- Fiction; Families -- Fiction; Mothers and sons -- Fiction; Family secrets -- Fiction; Saint John (United States Virgin Islands) -- Fiction; Domestic fiction